2017
DOI: 10.1167/iovs.16-21271
|View full text |Cite
|
Sign up to set email alerts
|

Caucasian Families Exhibit Significant Linkage of Myopia to Chromosome 11p

Abstract: PurposeMyopia is a common visual disorder caused by eye overgrowth, resulting in blurry vision. It affects one in four Americans, and its prevalence is increasing. The genetic mechanisms that underpin myopia are not completely understood. Here, we use genotype data and linkage analyses to identify high-risk genetic loci that are significantly linked to myopia.MethodsIndividuals from 56 Caucasian families with a history of myopia were genotyped on an exome-based array, and the single nucleotide polymorphism (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The linked variant and gene do not have any prior evidence of involvement in causation of myopia or eye disease in general. However other protein tyrosine phosphatase receptors have been associated or linked with myopia including PTPRR, PTPRF, and PTPRJ (Haw thorne et al 2013;Musolf et al 2017). Both PTPRR and PTPRF have been put forth as possible candidate genes for the MYP3 locus at 12q21-24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linked variant and gene do not have any prior evidence of involvement in causation of myopia or eye disease in general. However other protein tyrosine phosphatase receptors have been associated or linked with myopia including PTPRR, PTPRF, and PTPRJ (Haw thorne et al 2013;Musolf et al 2017). Both PTPRR and PTPRF have been put forth as possible candidate genes for the MYP3 locus at 12q21-24.…”
Section: Discussionmentioning
confidence: 99%
“…On the genetic side, population-based genome-wide association studies (GWAS) have identified multiple risk loci for a negative refractive error (Fan et al 2016;Kiefer et al 2013;Miyake et al 2015;Simpson et al 2014;Simpson et al 2013;Stambolian et al 2013;Verhoeven et al 2012;Verhoeven et al 2013), although the vast majority of these associations are to common variants with small to moderate effect. Family-based linkage studies have identified several linked regions that appear to harbor risk loci as well (Ciner et al 2009;Guo et al 2015;Musolf et al 2017;Stambolian et al 2004;Wojciechowski et al 2006;Zhou et al 2015). although the actual causal variant(s) at the linked and/or associated loci mostly remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of the F‐test and LRT statistics in a more realistic setting, we exploit exome chip genotypes and a quantitative trait, refractive error measured in Diopters, from Amish families that are part of the Myopia Family Study (Wojciechowski, Bailey‐Wilson, et al, ; Wojciechowski, Stambolian, et al, ). After sample quality checks using a thorough and rigorous data cleaning pipeline, which included checks for chromosomal aberrations, gender, Hardy–Weinberg equilibrium, relatedness, duplicates, and genotype quality, 300 genotyped and phenotyped individuals were available for analysis (see Wojciechowski, Bailey‐Wilson, et al, , for details of quality control on phenotype data; Musolf et al, , , for details of exome chip genotype data quality control processes). To completely specify the pedigree structures, we included nongenotyped or nonphenotyped individuals who shared the same family with phenotyped and genotyped family members.…”
Section: Methodsmentioning
confidence: 99%
“…The LMMs and FLMMs are an extension of traditional variance component models (Amos, ; Lange, ). We evaluate the performance of the LMMs and FLMMs via extensive simulations and illustrate their application by analyzing a complex trait, refractive error, with exome chip genotyping of Amish pedigrees (Musolf et al, , ; Wojciechowski, Bailey‐Wilson, & Stambolian, ; Wojciechowski, Stambolian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous data provided strong evidence that genetic factors also play a key role. Twin studies and genetic linkage analysis studies revealed a handful of potential loci for myopia-related genes [8, 9]. Recently, genome-wide association studies (GWAS) with large sample sizes identified more than 100 single nucleotide polymorphisms (SNPs) that influence myopia.…”
Section: Introductionmentioning
confidence: 99%